Rute Optimal Keterjangkauan Fasilitas Pelayanan Kesehatan Rumah Sakit terhadap Lokasi Rawan Kecelakaan di Kota Padang - Zulprima, Zulprima; Shahar, Fitriana (Lembaga Yasin AlSys, 2024)
This research aims to; 1) map the distribution of accident locations in Padang Timur Subdistrict. 2) analyze health service facilities to accident-prone points. 3) analyze the optimal route of accident-prone locations to public health facilities. This research method uses quantitative methods and the data used are secondary data and primary data. In getting the results of the distribution pattern of the location point, the researcher uses Averagea Nearest Neighbor while to get the results of the hospital coverage using the Service Area method. The results of this study found that the distribution of areas prone to traffic accidents in East Padang Sub-district in 2022 has a clustered pattern. It is known that the Nearest Neighbor Ratio value is 0.75; the z-score value is -2.17; and the p-value is 0.02. The range of hospitals to the location of traffic accidents on the Padang City Bypass highway has a range of 100 m - 2000 m, from six hospitals in East Padang Subdistrict, there are 15 traffic accidents that are reached and 6 traffic accidents that are not reached by the three hospitals.